The quest for CGIAR innovations to reduce food system carbon footprints on a global scale - Villarino, Maria Eliza J.; Castro-Nuñez, Augusto Carlos (CGIAR System Organization, 2022)
The Low-Emission Food Systems Initiative Mitigate+ aims to contribute to low-emission food systems development and reduce net annual greenhouse gas emissions from food systems. It forms part of CGIAR`s new research portfolio and includes IFPRI participation, delivering science and innovation to transform food, land, and water systems in a climate crisis. We, at work package 4 of Mitigate+, are on a mission to identify and scale CGIAR innovations with potential transformative effects—focusing now on the single largest global challenge: climate change. Now the question is: Which CGIAR innovations can be further scaled to achieve our goal while also continuing to contribute toward their initial aims of helping to reduce hunger and ensuring that people in the Global South have access to affordable and nutritious food? Scaling up innovations globally and achieving widespread adoption will require participation from key food system stakeholders.